The effect of altering body posture and barbell position on the between-session reliability of force-time curve characteristics in the isometric mid-thigh pull - Guppy, S. N.; Brady, C. J.; Kotani, Y.; Stone, M. H.; Medic, N.; Haff, G. G. (Sports, 2018)
Seventeen strength and power athletes (n = 11 males, 6 females; height: 177.5 ± 7.0 cm, 165.8 ± 11.4 cm; body mass: 90.0 ± 14.1 kg, 66.4 ± 13.9 kg; age: 30.6 ± 10.4 years, 30.8 ± 8.7 years), who regularly performed weightlifting movements during their resistance training programs, were recruited to examine the effect of altering body posture and barbell position on the between-session reliability of force-time characteristics generated in the isometric mid-thigh pull (IMTP). After participants were familiarised with the testing protocol, they undertook two testing sessions which were separated by seven days. In each session, the participants performed three maximal IMTP trials in each of the four testing positions examined, with the order of testing randomized. In each position, no significant differences were found between sessions for all force-time characteristics (p = >0.05). Peak force (PF), time-specific force (F50, F90, F150, F200, F250) and IMP time-bands (0-50, 0-90, 0-150, 0-200, 0-250 ms) were reliable across each of the four testing positions (ICC = 0.7, CV = 15%). Time to peak force, peak RFD, RFD time-bands (0-50, 0-90, 0-150, 0-200, 0-250 ms) and peak IMP were unreliable regardless of the testing position used (ICC = <0.7, CV = >15%). Overall, the use of body postures and barbell positions during the IMTP that do not correspond to the second pull of the clean have no adverse effect on the reliability of the force-time characteristics generated.